2016
DOI: 10.1134/s1607672916010130
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic bacterial community profiles of chicken embryo gastrointestinal tract by using T-RFLP analysis

Abstract: Thirty microbial phylotypes of microorganisms were found in the gastrointestinal tract of chicken belonging to the Hajseks White breed, and 38 phylotypes were found in the gastrointestinal tract of chicken belonging to the Hajseks Brown breed. The microbiome of the gastrointestinal tract of the chicken embryos of the Hajseks White breed was dominated by the typical representatives of avian intestinal microflora--bacteria of the family Enterobacteriaceae (47.3%), orders Actinomycetales (13.6%) and Bifidobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Lower UniFrac distance from ceca to extraintestinal sites (blood, femur and tibia) and spatiotemporal distribution of microbiota at day 1 may suggest the gut as the source of extraintestinal microbiota ( Figures 5 , 6 ). Ilina et al ( 26 ) discovered 38 phylotypes of microbiota were able to colonize the gastrointestinal tract of the chicken embryo using terminal restriction fragment length polymorphism (T-RFLP). However, higher alpha diversity index (OTUs, Chao 1 and PD_whole_tree) in the extraintestinal site of chicks than ceca at day 1 portrays a different story.…”
Section: Discussionmentioning
confidence: 99%
“…Lower UniFrac distance from ceca to extraintestinal sites (blood, femur and tibia) and spatiotemporal distribution of microbiota at day 1 may suggest the gut as the source of extraintestinal microbiota ( Figures 5 , 6 ). Ilina et al ( 26 ) discovered 38 phylotypes of microbiota were able to colonize the gastrointestinal tract of the chicken embryo using terminal restriction fragment length polymorphism (T-RFLP). However, higher alpha diversity index (OTUs, Chao 1 and PD_whole_tree) in the extraintestinal site of chicks than ceca at day 1 portrays a different story.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the bacterial community in the caecum of birds was examined by the terminal restriction fragment length polymorphism (T-RFLP) method [90,91,92,93]. T-RFLP based on the analysis of the nucleotide sequences of the 16S rRNA gene is a fairly reliable and up-to-date technique for analysing the microflora of complex communities including those in the gut lumen of chickens [94], and its results are comparable to those obtained using high-throughput sequencing [95].…”
Section: Methodsmentioning
confidence: 99%
“…Binek et al ( 94 ) reported results revealing the identification of similar microbial populations: Entercoccus sp., Micrococcus sp., and Bacillus sp. Additionally, Ilina et al ( 96 ) used terminal restriction fragment length polymorphism (T-RFLP) to determine the structure and composition of the microbial populations present in the GITs of chick embryos on the 16th day of incubation in two different breeds of Hajseks chickens (Brown and White breeds). This study indicated that by 16 days of incubation, the chick embryo contains microbiota with relatively rich taxonomic diversity, reporting that the Hajseks Brown breed samples to contained 38 different phylotypes, while 30 were observed in the Hajseks White breed samples ( 96 ).…”
Section: Git Microbiome Developmentmentioning
confidence: 99%